2019
DOI: 10.13057/biodiv/d200640
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial characterization of alginate extracted from Sargassum polycystum collected from three habitats in Banten, Indonesia

Abstract: Abstract. Dharmayanti N, Supriatna J, Abinawanto, Yasman. 2019. Isolation and partial characterization of Alginate from Sargassum polycystum of Banten, Indonesia. Biodiversitas 20: 1776-1785. The utilization of Sargassum polycystum as an alternative alginate source may reduce the dependence on alginate import as currently alginate demands in Indonesia are 100% supplied from overseas. The purpose of this study was to characterize alginate extracted from Sargassum polycystum obtained from three locations with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
(7 reference statements)
0
2
1
Order By: Relevance
“…Additionally, the proper extraction process, habitat, and lifespan of macroalgae can also affect the yield value. This is in accordance with Dharmayanti et al (2019) who stated that the yield of alginate produced from seaweed is influenced by habitat (light intensity, small wave, or current and aquatic nutrients), the age of brown seaweed, and brown seaweed handling techniques after harvesting and before and the extraction process used. Similarly, according to Sinurat and Marliani (2017), the high yield value in alginate shows that the better the extraction process is carried out and can increase the economic value of alginate.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, the proper extraction process, habitat, and lifespan of macroalgae can also affect the yield value. This is in accordance with Dharmayanti et al (2019) who stated that the yield of alginate produced from seaweed is influenced by habitat (light intensity, small wave, or current and aquatic nutrients), the age of brown seaweed, and brown seaweed handling techniques after harvesting and before and the extraction process used. Similarly, according to Sinurat and Marliani (2017), the high yield value in alginate shows that the better the extraction process is carried out and can increase the economic value of alginate.…”
Section: Discussionsupporting
confidence: 89%
“…While at the base, the moisture content is low because the base has formed guluronic acid and mannuronic acid, which have hydrophilic properties that bind water, increasing the amount of water trapped in guluronic acid and mannuronic acid. According to Dharmayanti et al (2019), the moisture content in alginate is between 5-20%, while the moisture allowed by the FCC ( 2004) is <15%. JECFA also stated that the moisture cotent of food additives of alginate is maximum at 15% (FAO, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…According to the data, the alginate generated in this study has a viscosity value that is a poor grade. It is lower than previous studies, such as Dharmayanti et al (2019), with 81.33 cP from S. polycystum grown in the western part of Java, but higher than those Anwar et al (2013), with 14.33 to 23.33 cP from S. duplicatum grown in Jepara, Central Java, and only 14.10 cP and 17.22 cP from Caribbean Sargassum and Macrocystis pyrifera, respectively (Mohammed et al, 2020b;Paul et al, 2020). Furthermore, " Draget et al, 1994" produced an alginic acid viscosity of 14.8 cP in the stipe thallus and 14.2 cP in the leaves using Laminaria hyperborea seaweed.…”
Section: Viscositycontrasting
confidence: 65%
“…A review by Hernández-Carmona et al ( 2013) discovered that the commercial-use moisture property criterion must be less than 12%. Other studies revealed that the moisture content of alginate obtained from S. polycystum growth in Banten, Indonesia was 10.23-13.31% (Dharmayanti et al, 2019), S. polycystum growth in Sebesi island was 12.16 %% Sumandiarsa et al (2020), and Sargassum fluitans growth in Alor waters, East Nusa Tenggara was low at 9.35% (Maharani et al, 2017).…”
Section: Moisture Contentmentioning
confidence: 96%
“…In Indonesia, seaweed is a commodity that is abundant and easy to find in coastal waters [15]. Alginate is a heteropolysaccharide compound group that has two monomers [17]. The monomers are chain monomers mannuronic acid (poly-Dmannuronic acid) and guluronic acid (poly-Lguluronic acid) [12].…”
Section: Introductionmentioning
confidence: 99%